The Characteristics of Relationship Between Consumers and State-Owned Gas Company in Implementing a Project of Domestic Gas Installation System - Ghansham Anand; Dyah Ismi Afifah (Fakultas Hukum Universitas Hang Tuah, 2017)
A project of one million domestic gas installations across Indonesia has been implemented by PT Perusahaan Gas Negara (PGN) since 2014. However, the right and obligation between the company and consumers who installed the domestic gas is not clearly stated. This may cause a right dispute between them when it comes to an unexpected occurrence. Whereas, their relationship is important as it relates to some aspects of consumer protection and obligation, which may lead into claims when something bad happen. Based on Article 19 of the Act of 1999 No. 8 about Consumer Protection, an enterprise is responsible to give compensations in the form of cash money or other similar goods/services with equal value or medical treatment and/or insurance. In regard to consumer‟s liability, they have to provide evidence. The liability of the enterprise is classified into a liability of guilt by shifting the weight of evidence. It is mentioned in Article 28 UUPK that if an enterprise is unable to prove that it is not guilty or if it is found guilty conducting action against its liability of law, the enterprise has to give compensation to its consumers, who feel disadvantageous. The basis of applying that claim toward the enterprise points to the lack of performance or legal violence.